Tests on Pretrained Superelastic NiTi Shape Memory Alloy Rods: Towards Application in Self-Centering Link Beams - Xian Xu; Guangming Cheng; Junhua Zheng (Advances in Civil Engineering)
Austenitic shape memory alloy has potential applications in self-centering seismic resistant structural systems due to its superelastic response under cyclic tension. Raw austenitic SMA needs proper pretreatments and pretraining to gain a stable superelastic property. In this paper, tests are carried out to investigate the effects of pretraining, pretreatments, loading rate, and strain amplitude on the mechanical performance on austenitic SMA rods with a given size. The tested rods are to be used in a new concept self-centering steel link beam. Customized pretraining scheme and heat treatment are determined through the tests. The effects of loading rate and strain amplitude are investigated. A simplified stress-strain model for the SMA rods oriented to numerical simulations is obtained based on the test results. An example of using the simplified material model in numerical analysis of a self-centering steel link beam is conducted to validate the applicability of the model.